Augmentation of gonadotropin-releasing hormone receptor expression in the post-lactational mammary tissues of rats - TERASHIMA, Ryota (J Reprod Dev, 2016)
Gonadotropin-releasing hormone (GnRH) is a neurohormone of the hypothalamus controlling pituitary gonadotropin secretion and hence gametogenesis. While it has also been believed that GnRH is synthesized and functions in various peripheral tissues, the expression of GnRH receptor (GnRH-R) in peripheral tissues is not well-described. We previously found that annexin A5, which is increased in the pituitary gonadotropes by GnRH, is dramatically increased in rat mammary epithelial cells after weaning, suggesting that local GnRH is responsible for this increase. Annexin A5 is a member of the annexin family of proteins and is thought to be involved in various regulatory mechanisms, including apoptosis. In the present study, we examined GnRH-R expression in the mammary tissues after weaning. Although GnRH-R mRNA was not detected in the mammary tissues during lactation, it was dramatically increased after weaning. Forced weaning at mid-lactation (day 10) also promoted the expression of GnRH-R transcripts in mammary tissues within 2 days. Furthermore, western blotting analysis with anti-GnRH-R showed that the expression of an immuno-positive 60-kDa protein, whose size was equivalent to that of rat GnRH-R, was confirmed to increase after weaning. These findings clarified the induction of GnRH-R in the mammary tissues after weaning and suggest that GnRH is involved in the involution and tissue remodeling of post-lactating rat mammary tissues.